The Role of Meaningful Work as a Mediation of Political Organizations on Employee Engagement - Muh Daud; Dian Novita Siswanti; Dwi Yan Nugraha (Jurnal Psikologi Perseptual)
Employee engagement can generate benefits for the organization and lead to positive work outcomes. However, sometimes the application of organizational politics can affect performance. Thus, meaningful work is needed for employees. The aim of this research is to examine the role of meaningful work mediation on the influence of political organizations on employee engagement. This study used a quantitative method with a cross-sectional survey design. The sample of this research is 317 employees obtained using convenience sampling technique. The scale in this study consists of employee engagement, meaningful work, and political organizations using a five-point Likert model. The results obtained in this study are significant meaningful work mediating the influence of political organizations on employee engagement. This study contributes as reference material in implementing interventions to increase employee engagement in order to gain benefits for the organization.